Efektivitas Media Promosi Kesehatan Terhadap Pengetahuan dan Sikap Siswa Tentang Pengelolaan Sampah di SMP Negeri 6 Birem Bayeun Kabupaten Aceh Timur - Etika Sari; Eka Lestari (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2026)
Organic and inorganic waste is often left to accumulate behind the school or burned, which can cause air pollution and threaten the health of the surrounding environment. This study aims to determine the effectiveness of health promotion media on students' knowledge and attitudes about waste management at SMP Negeri 6 Birem Bayeun, East Aceh Regency. Method: This research is a quantitative study with a quasi- experiment design using a one-group pretest-posttest design. The total sample in this study was 98 respondents, which were divided into two groups: 49 students received intervention through video media and 49 students through leaflets. The sampling technique used simple random sampling, and data analysis was conducted using the Wilcoxon Signed-Rank test. Results: The results of the analysis showed that the average knowledge score after the video and leaflet media intervention had a p=0.000 value, indicating a significant increase. However, the average attitude score after the intervention showed a value of p=0.266, which was not significant. Mann- Whitney test showed no difference in effectiveness between video and leaflet media.Conclusion: It is recommended that schools work together with the government to address waste management issues, so that the practice of burning waste can be minimized for better health and environment.